Breakdown film script using parsing algorithm - Agung Wahana; Diena Rauda Ramdania; Dhanis Al Ghifari; Ichsan Taufik; Faiz M. Kaffah; Yana Aditia Gerhana (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Breakdown script is a breakdown of the scenario into parts that describe each detail of the scene for shooting. The scenario is broken down into more detailed parts using the parsing algorithm. The film script used is a script in Bahasa Indonesia. The process starts from the film script file/scenario in FBX format uploaded to the website then is solved using a parsing algorithm into film elements such as cast members, extras, props, costumes, makeup, vehicles, stunts, special effects, music and sound. The results of this breakdown into sheets according to film elements. The purpose of this research is to produce breakdown sheets from film scripts according to film elements. The parsing algorithm test results showed the correct results of 12 scenes out of 19 scenes.